Joint US-India international symposium : Papers (Rotterdam, 1992)
Traditional aquaculture has been in vogue for centuries in countries such as China and India. It is only in the recent past, however, that the traditional art of aquaculture became a well-defined science with the research support and development of near exacting technologies. In the present time, aquaculture assumes all the more importance now, when fish production from capture fishery resources is fast reaching its limits and the natural resources are in the danger of over exploitation. A joint US-India sponsored international symposium was held in New Delhi in 1988. This publication brings together the revised and edited versions of the contributions made by experts in the field. The authors address various aspects related to aquaculture such as genetics, nutrition, reproduction physiology and endocriniology, diseases, economics, extension, social issues and production systems from different countries. The recommendations made by the scientists serve as a review of the status of aquaculture as a science practised globally.
Keywords: Aquaculture; Research